A new solar energy-based system integrated with hydrogen storage and heat recovery for sustainable community - Erdemir, Dogan; Dincer, Ibrahim (ELSEVIER, 2022)
This study presents a unique solar energy-based system using green hydrogen as energy storage option developed to meet the electricity, heat and cooling demands for a potentially sustainable community. The energy and exergy analyses are implemented to analyse and assess the proposed system and its performance. In this regard, a community is identified in the Southern Ontario in Canada with 1500 residential units. The hydrogen produced in the system is stored in the underwater balloons, called the underwater hydrogen balloon. The heat recovery from the sewage is included in the system in order to enhance the performance of the air conditioners and heat pumps. The results of the present study indicate that in order to dedicate the off-grid power system, 288,000 m(2) of PV panels is required in the month of December when the lowest solar radiation is obtained. On the hand, it is possible to provide 65,474 kWh of energy can be provide the grid with that much of PV panel in the month of June. Both energy and exergy efficiency values tend to decrease with the increasing both PV panel area and solar radiation due to increasing solar energy input against to constant demand items. The heat recovery from the sewage helps increase the performance of the air contioning system with heat pump by about 33%.
Keywords: Energy storage; Hydrogen; Multigeneration; Renewable energy; Sustainable community; Heat recovery; Exergy; Efficiency; Science & Technology - Other Topics; Energy & Fuels